2018
DOI: 10.1038/s41467-018-07393-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal degradation of BRAHMA promotes Boron tolerance in Arabidopsis

Abstract: High levels of boron (B) induce DNA double-strand breaks (DSBs) in eukaryotes, including plants. Here we show a molecular pathway of high B-induced DSBs by characterizing Arabidopsis thaliana hypersensitive to excess boron mutants. Molecular analysis of the mutants revealed that degradation of a SWItch/Sucrose Non-Fermentable subunit, BRAHMA (BRM), by a 26S proteasome (26SP) with specific subunits is a key process for ameliorating high-B-induced DSBs. We also found that high-B treatment induces histone hyperac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 57 publications
1
56
0
Order By: Relevance
“…Therefore, cell wall-mediated boron toxicity alone may not explain the toxic effects of excess boron on these systems, especially animal cells. Excess boronassociated DNA damage has been reported as a consequence of boron toxicity among eukaryotes (Sakamoto et al, 2018). In addition, we showed that transcriptional signals related to RNA metabolism were substantially affected in A. thaliana, while S. parvula orthologs showed a stress-prepared expression level prior to the stress ( Figure 4A, 6A, and 6B).…”
Section: Why Is Excess Boron Toxic To Plants?mentioning
confidence: 56%
“…Therefore, cell wall-mediated boron toxicity alone may not explain the toxic effects of excess boron on these systems, especially animal cells. Excess boronassociated DNA damage has been reported as a consequence of boron toxicity among eukaryotes (Sakamoto et al, 2018). In addition, we showed that transcriptional signals related to RNA metabolism were substantially affected in A. thaliana, while S. parvula orthologs showed a stress-prepared expression level prior to the stress ( Figure 4A, 6A, and 6B).…”
Section: Why Is Excess Boron Toxic To Plants?mentioning
confidence: 56%
“…Interestingly, while BRM was enriched near transcriptional start sites (TSS) of target genes as expected, many target genes were bound at their 3 end, especially at 3 regions that have promoter-like structures such as TATA boxes, high H3K4me3 levels, low H3K27me3 and di-methylated lysine 9 on H3 (H3K9me2) levels, and high antisense transcriptional activity. However, BRM does not co-localize with the H3K27me3 mark [22] but with H3K9 and H3K14 acetylation marks [27].…”
Section: Genome-wide Functions Of Brm In Plantsmentioning
confidence: 87%
“…BRM stability is also involved in DNA double-strand breaks (DSBs) tolerance in Arabidopsis [27]. High levels of boron induce DSBs.…”
Section: Brm Has Roles In Abiotic Stress and Hormone Pathwaysmentioning
confidence: 99%
“…Inhibition of cell division in the RAM is a critical cause of B toxicity in roots. In roots of Arabidopsis thaliana , high-B treatment decreases the RAM size through inhibition of cell division activity (Sakamoto et al, 2011, 2018; Aquea et al, 2012). The reduction in cell division activity is also observed in root tips of Vicia faba treated with a high B concentration (Liu et al, 2000), The inhibition of cell division is attributed to DNA damage caused by high-B stress in the RAM (Sakamoto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in cell division activity is also observed in root tips of Vicia faba treated with a high B concentration (Liu et al, 2000), The inhibition of cell division is attributed to DNA damage caused by high-B stress in the RAM (Sakamoto et al, 2011). We previously reported that a chromosomal protein complex (condensin II) and a regulatory particle AAA-ATPase 5a (RPT5a) of 26S proteasome (26SP) are essential for amelioration of high-B-dependent DNA damage and the maintenance of RAM size in A. thaliana (Sakamoto et al, 2011, 2018).…”
Section: Introductionmentioning
confidence: 99%